Economic Criteria for Lithuanian’s Membership in the European Union and the Outlook of their Fulfilment - Šimėnas, Albertas (Ekonomika, 1998)
Together with other countries of Central and Eastern Europe, Lithuania seeks to integrate into EU’s political and economic space, In the opinion of the European Commission, the existing relations of market economy and progress of economy does not yet satisfy the requirements raised before the future members of the EU. The majority of remarks laid down by the Commission in its evaluation of the process of economic reforms and the condition of economy of Lithuania, concern companies, banking sector, energy industry, agriculture and public finances. The article analyses situation in these sectors and the trends of their development vis-a-vis the criteria established by the EU. Analysis of the GDP, rate of inflation and other key macroeconomic indicators reveals positive tendencies, enabling to maintain a stable 4-5% economy growth in Lithuania. This would make it possible for Lithuania to overcome the existing deficiencies and meet requirements raised by the EU. In terms of distribution by branches, separate branches of the industry are facing the best perspectives for development (e.g. clothing, leather, textile, food, oil refining, timber processing and furniture industries), also the sectors of energy industry, transport and communications. The largest problems lie in the agrarian and environment protection sectors. The central conclusion of the article maintains that the analysis of the economic criteria for membership in the EU and the trends of Lithuania’s economy permit to say that Lithuania can reasonably look forward to membership in the European Union in 2000-2008.